2015
DOI: 10.3892/ijmm.2015.2088
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor improves the migration and contractility of aged fibroblasts cultured on 3D collagen matrices

Abstract: Abstract. Epidermal growth factor (EGF) plays a critical role in fibroblasts by stimulating the production of collagen and supports cell renewal through the interaction between keratinocytes and fibroblasts. It is well known that the contractile activity of fibroblasts is required for the remodeling of the extracellular matrix (ECM), which contributes to skin elasticity. However, the role of EGF in the contraction of aged fibroblasts under 3-dimensional (3D) culture conditions is not yet fully understood. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
1
30
0
1
Order By: Relevance
“…Aberrant persistence of EGFR signaling can lead to hypertrophic scars or keloid scars [31,32], partially due to paracrine upregulation of EGFR on fibroblasts [33]. Aged dermal fibroblasts exhibit reduced EGFR expression, and this decline correlates with decreased responsiveness to EGFR mitogenic signaling, manifested in delayed healing and reduced scarring [30,34].…”
Section: Fibroblastic Cell Plasticitymentioning
confidence: 99%
“…Aberrant persistence of EGFR signaling can lead to hypertrophic scars or keloid scars [31,32], partially due to paracrine upregulation of EGFR on fibroblasts [33]. Aged dermal fibroblasts exhibit reduced EGFR expression, and this decline correlates with decreased responsiveness to EGFR mitogenic signaling, manifested in delayed healing and reduced scarring [30,34].…”
Section: Fibroblastic Cell Plasticitymentioning
confidence: 99%
“…The increase in cell contractility with MDA-CM was confirmed by the measurement of stress-related collagen matrix contraction (SRMC) which is a typical method for evaluating cell contractility induced by mechanical tension 29 . SRMC under MDA-CM increased profoundly, while the extent of SRMC with 10A-CM was similar to that of control medium ( Fig.…”
Section: Resultsmentioning
confidence: 87%
“…This study also indicated EGF-MSCs as a useful cell therapy approach for hypertrophic scars. Interestingly, a recent investigation demonstrated that rhEGF improved the migration and contraction of aged fibroblasts more efficiently than young fibroblasts under three-dimensional culture conditions [76]. These findings implied that rhEGF might have regenerative effects on aged skin and highlighted the therapeutic value of EGF for hypertrophic scars in aged populations.…”
Section: Epidermal Growth Factor Pathwaymentioning
confidence: 97%